2009
DOI: 10.1186/1471-2393-9-s1-s7
|View full text |Cite
|
Sign up to set email alerts
|

Delivering interventions to reduce the global burden of stillbirths: improving service supply and community demand

Abstract: Background: Although a number of antenatal and intrapartum interventions have shown some evidence of impact on stillbirth incidence, much confusion surrounds ideal strategies for delivering these interventions within health systems, particularly in low-/middle-income countries where 98% of the world's stillbirths occur. Improving the uptake of quality antenatal and intrapartum care is critical for evidence-based interventions to generate an impact at the population level. This concluding paper of a series of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
116
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(122 citation statements)
references
References 139 publications
3
116
1
2
Order By: Relevance
“…Although few studies have been done in lowincome and middle-income countries, reported eff ect sizes range from small to moderate for improved provider prac tices [61][62][63] and are large for drug management 64 and perinatal and intrapartum mortality. 64,65 Increased supervision is another strategy used to improve health-worker performance in low-income and middle-income countries and has moderate-to-large eff ects.…”
Section: Improving Continuity Of Carementioning
confidence: 99%
“…Although few studies have been done in lowincome and middle-income countries, reported eff ect sizes range from small to moderate for improved provider prac tices [61][62][63] and are large for drug management 64 and perinatal and intrapartum mortality. 64,65 Increased supervision is another strategy used to improve health-worker performance in low-income and middle-income countries and has moderate-to-large eff ects.…”
Section: Improving Continuity Of Carementioning
confidence: 99%
“…To support the basic primary health care infrastructure, a range of different approaches have been developed to train CHWs to provide specific tasks related to antenatal and postnatal care [216,277]. These trained CHWs deliver these interventions to the community via different strategies, such as community mobilization and home visitation.…”
Section: Community Based Intervention Packages (Community Mobilizatiomentioning
confidence: 99%
“…Impact estimates: The review by Hundley et al [213] identified intervention packages which include CDKs to reduce risk for maternal puerperal sepsis (OR 0.17; 95% CI: 0.13 to 0.23) [214], neonatal infectious morbidity such as sepsis (RR 0.12; 95% CI: 0.02 to 0.93) [215], and omphalitis (OR 0.42; 95% CI: 0.18 to 0.97 [215]; (OR 0.08; 95% CI: 0.03 to 0.19) [216,217]. Available studies show that the provision of CDKs has a statistically significant impact on perinatal/ neonatal mortality ((OR 0.7; 95% CI: 0.59 to 0.82) [79]; (RR 0.17; 95% CI: 0.13 to 0.23) [214,218,219]; (OR 0.78; 95% CI: 0.50 to 1.21) [29]).…”
Section: Provision Of Clean Delivery Kitsmentioning
confidence: 99%
“…9,21,22 In these situations, it may not always be possible to transfer a woman to an emergency obstetric care facility in time to perform a life-saving procedure should the need arise. [23][24][25] Furthermore, as more emphasis is placed on delivery at health-care facilities and as women become more aware of the benefits, there has been an increase in the workload at referral hospitals in low-resource areas, many of which are underequipped and understaffed. [25][26][27] Thus, even when a referral is made, the quality of care is often inadequate, especially for women who arrive late with a complication.…”
Section: Introductionmentioning
confidence: 99%